Pet acquisition trends and veterinary care access in the US - Courtney Bir; Kayla Pasteur; Nicole Widmar; Candace Croney (PLoS ONE, 2025)
The COVID-19 pandemic presented a host of unique challenges for individuals worldwide, particularly for pet owners, due to widespread shutdowns, social distancing, and financial stress. While pet acquisition increased during this time, the impact on veterinary care access and pet ownership trends remain underexplored. Within the online survey of 751 US residents 79% were pet owners (n = 596). Twenty percent of all pet owners reported difficulty accessing basic veterinary care, such as vaccinations or annual exams. Logit models revealed that having children and working from home increased the likelihood of acquiring a pet during the pandemic. Additionally, owning a pet acquired during the pandemic and managing pets with behavioral issues were associated with greater challenges in accessing veterinary care. These findings highlight unique circumstances during COVID-19 related to pet acquisition and veterinary care, which may be expanded to other situations. A better understanding of these difficulties is essential to develop solutions that protect animal welfare and support the human-animal bond, particularly in times of crisis.